2005
DOI: 10.1111/j.1365-2095.2004.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial substitution of fish oil with rapeseed, linseed and olive oils in diets for European sea bass (Dicentrarchus labrax L.): effects on flesh fatty acid composition, plasma prostaglandins E2 and F2alpha, immune function and effectiveness of a fish oil finishing diet

Abstract: Triplicate groups of European sea bass (Dicentrarchus labrax L.), of initial weight 90 g, were fed four practical‐type diets in which the added oil was 1000 g kg−1 fish oil (FO) (control diet), 600 g kg−1 rapeseed oil (RO) and 400 g kg−1 FO, 600 g kg−1 linseed oil (LO) and 400 g kg−1 FO, and 600 g kg−1 olive oil (OO) and 400 g kg−1 FO for 34 weeks. After sampling, the remaining fish were switched to the 1000 g kg−1 FO diet for a further 14 weeks. Fatty acid composition of flesh total lipid was influenced by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
129
3
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(180 citation statements)
references
References 67 publications
38
129
3
7
Order By: Relevance
“…Lipoid livers, due to severe fatinfiltration, were also shown after high levels of LO or SFO intake (LO/SFO70 diets) especially for SFO-fed fish, indicating that dietary lipid exceeded the capacity of the hepatic cells to oxidize fatty acids, or due o protein synthesis impairment (Watanabe, 1982) which resulted in large synthesis and deposition of triglycerides (TAGs) in vacuoles, leading to that morphological pattern known as steatosis or lipoid liver. Results of the present study are in broad agreement with earlier findings in other fish species such as European seabass (Mourente et al, 2005). They reported that accumulation of lipid droplets in the livers of fish fed LO and rapeseed oil (RO) diets may be due to the preference for specific FAs as energy sources resulting in storage of surplus FAs (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Lipoid livers, due to severe fatinfiltration, were also shown after high levels of LO or SFO intake (LO/SFO70 diets) especially for SFO-fed fish, indicating that dietary lipid exceeded the capacity of the hepatic cells to oxidize fatty acids, or due o protein synthesis impairment (Watanabe, 1982) which resulted in large synthesis and deposition of triglycerides (TAGs) in vacuoles, leading to that morphological pattern known as steatosis or lipoid liver. Results of the present study are in broad agreement with earlier findings in other fish species such as European seabass (Mourente et al, 2005). They reported that accumulation of lipid droplets in the livers of fish fed LO and rapeseed oil (RO) diets may be due to the preference for specific FAs as energy sources resulting in storage of surplus FAs (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the increase in the levels of DHA from fish fed diets with low dietary levels of this fatty acid has led to speculate that DHA was selectively retained in fish muscles compared to other fatty acids. Similar observations were also reported for bigger sizes of the species (∼130 g/fish) fed a vegetable oils blend for 20 weeks (Wassef et al, 2009(Wassef et al, , 2012 and for European seabass (Dicentrarchus labrax) as well (Mourente et al, 2005). In the present study, the relatively less DHA deposition in the muscle with LO70 diet than with SFO70 diet (Tab.…”
Section: Discussionsupporting
confidence: 77%
“…European sea bass, Dicentrarchus labrax, is a strict carnivorous marine fish and it has been suggested to have extremely low rates of PUFA bioconversion (Mourente et al, 2005a;Mourente et al, 2005b). Nevertheless, the enzyme Δ-6 desaturase was recently cloned and characterized in European sea bass (Santigosa et al, 2011), and in vivo production of the products of all the enzymes involved in the elongation and desaturation of C 18 PUFA (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As with all vertebrates, PUFA are essential in the diet of fish, but requirements vary with species, with marine fish having a dietary requirement for HUFA such as EPA and DHA, rather than shorter chain PUFA found in vegetable oil (Tocher, 2003). Feeding marine fish vegetable oil can reduce growth and lead to health problems including increased fat deposition and fatty livers, and compromised immune function (Caballero et al, 2004;Bell et al, 2005;Mourente et al, 2005).…”
Section: Introductionmentioning
confidence: 99%